Hierarchical Cluster Analysis of Multicenter Development and Travel Patterns in Istanbul - Ozus, Evren; Akin, Darcin; Ciftci, Murat (ASCE-AMER SOC CIVIL ENGINEERS, 2012)
This paper investigates the multicenter development course of Istanbul based upon urban travel patterns in the city. The spatial distribution of population and employment between 1970 and 2000 illustrated a decentralizing trend in the urban structure. Hierarchical clustering analysis was used to determine relatively homogenous groups of interactions and to explain the interaction patterns among the districts. The results of the study supported the multicenter development at the lower level on both continents ( Asia and Europe), and at the upper level between the continents. Determination of efficient locations of new subcenters was suggested for further research. DOI: 10.1061/(ASCE)UP.1943-5444.0000121. (C) 2012 American Society of Civil Engineers.
Keywords: Hierarchical cluster; Multicenters; Travel pattern; Labor economics and economic demography; Istanbul; CITY-CENTER; URBAN FORM; EMPLOYMENT; IMPACT; DECENTRALIZATION; REVITALIZATION; SUBCENTERS; VALUES; MODELS; SIZE; Engineering; Public Administration; Urban Studies